Mediastinal paragangliomas related to SDHx gene mutations - Michałowska, Ilona; Ćwikła, Jarosław; Prejbisz, Aleksander; Kwiatek, Paweł; Szperl, Małgorzata; Michalski, Wojciech; Wyrwicz, Lucjan; Kuśmierczyk, Mariusz; Januszewicz, Andrzej; Maciejczyk, Anna; Roszczynko, Marta; Pęczkowska, Mariola (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction : Paragangliomas (PGLs) related to hereditary syndromes are rare mediastinal tumors. Paragangliomas are caused by mutations in genes encoding subunits of succinate dehydrogenase enzyme (SDH). Aim: To evaluate clinical, anatomical and functional characteristics of mediastinal paragangliomas related to SDHx gene mutations. Material and methods : Retrospective analysis of 75 patients with confirmed SDHx gene mutations (24 patients with SDHB , 5 SDHC , 46 with SDHD mutations) was performed. Patients underwent evaluation using computed tomography (CT), somatostatin receptor scintigraphy (SRS) ( 99m Tc-[HYNIC,Tyr3]-octreotide), 123 I mIBG scintigraphy and urinary excretion of total methoxycatecholamines. Results : Out of 75 patients, 16 (21%) patients (1 SDHB , 15 SDHD mutations) had 17 PGLs localized in the mediastinum. Fourteen PGLs were localized in the middle mediastinum (intrapericardial) and 3 PGLs in the posterior mediastinum. The median diameter of paragangliomas measured on the axial slice was 24.3 mm (interquartile range (IQR): 14.7–36.6), and the median volume was 2.78 ml (IQR: 0.87–16.16). Twelve out of 16 patients (75%) underwent SRS, and 11 of them (92.3%) had pathological uptake of the radiotracer. Eleven (68.75%) out of 16 patients underwent 123 I mIBG, with only 3 positive results. Symptoms of catecholamine excretion were observed in 3 patients with PGLs localized in the posterior mediastinum. All PGLs were benign except in 1 patient with the SDHB mutation and PGL detected in the posterior mediastinum, who had a metastatic disease. Conclusions : Most mediastinal paragangliomas were related to SDHD gene mutations. They were asymptomatic, localized in the medial mediastinum, intrapericardially.